Dynamic column loss analysis of reinforced concrete flat slabs. (1st November 2019) - Russell, J.M.; Owen, J.S.; Hajirasouliha, I.
Highlights: A dynamic column loss finite element model was validated against experimental data. Different material and geometry properties were considered for a full floor model. Dynamic amplification factors were dependant of the extent of nonlinearity. Concrete strength increase due to strain rate effects does not change the response. Abstract: The sudden column loss idealisation is a useful design tool to assess structures for progressive collapse. As such an event is a dynamic problem, suitable account must be taken of these effects. This can either be achieved by a full dynamic analysis of the structure or a simplified static approach, with correction factors for the dynamic influence. This study aims to investigate the response of Reinforced Concrete (RC) flat slab structures after a column loss using experimentally validated Finite Element (FE) models. The nonlinear dynamic response of a structure after such an event is considered, including the redistribution of loads and displacement profile. These results are then compared to equivalent static cases in order to determine the Dynamic Amplification Factor (DAF). For the range of structures considered, the DAF was calculated as between 1.39 and 1.62 for displacements, with lower factors associated with a higher nonlinear response or slower column removal. Additionally, the shear forces in remaining columns may exceed 200% of their fully supported condition, with a different associated DAF. The effects of increasing the tensile strength of concrete due to high strain rates are also considered. Typical Dynamic Increase Factors (DIFs) based on the strain rates were up to 1.23, however, this only applied for a short time period, and in a limited area. Therefore, such effects do not significantly influence the response.